2013
DOI: 10.3928/01477447-20130821-11
|View full text |Cite
|
Sign up to set email alerts
|

Posterolateral Corner of the Knee: Microsurgical Analysis of Anatomy and Morphometry

Abstract: Reconstruction of the posterolateral corner (PLC) of the knee is essential to restore knee joint function. Controversy exists regarding a standardized nomenclature, the connective attachments and the relationships between them, and the frequency of occurrence among all structures of the PLC. Thirty human cadaveric knee specimens were investigated. The lateral collateral ligament, popliteus tendon, popliteofibular ligament, fabellofibular ligament, arcuate ligament, oblique popliteal ligament, posterior menisco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 25 publications
(43 reference statements)
3
22
1
Order By: Relevance
“…The mean length and width of the popliteus tendon in present study was 35.12 mm and 9.52 mm, respectively. This is almost similar to most of the previous studies (15,16). The length of popliteal tendon in present study was found to be shorter than that reported by Kurtoglu et al (17).…”
Section: Discussionsupporting
confidence: 92%
“…The mean length and width of the popliteus tendon in present study was 35.12 mm and 9.52 mm, respectively. This is almost similar to most of the previous studies (15,16). The length of popliteal tendon in present study was found to be shorter than that reported by Kurtoglu et al (17).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding about the length of LCL was similar to previous studies, as shown in Table II (Maynard et al, 1996;Ishigooka et al, 2004;Espregueira-Mendes & da Silva;Zhang et al, 2009;Jung et al;Osti et al). In most of the cases, LCL was wider at the upper part and narrower at the lower part, in accordance with the findings of Takeda et al In these literatures, width of LCL was given from the midportion or at the level of articular line.…”
Section: Lateral (Fibular) Collateral Ligamentsupporting
confidence: 91%
“…Additionally, inconsistency in nomenclature of the ligamentous structures of the region (the fabellofibular ligament, arcuate popliteal ligament (AL) and PF) makes the area more difficult to cope with. The discrepancies for these ligaments have already been tried to be clarified by several authors and also the authors of previously presented study (Seebacher et al, 1982;Osti et al, 2013& Kurtoglu et al, 2015. For the PLC injuries, many reconstruction techniques have been published in the literature (Djian;Jung et al;Niki et al, 2012& Minowa et al, 2005.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, the reported incidence of MLIK was far greater than the morbidity of knee dislocation, especially in Chongqing, China. Although this observation may appear rudimentary, in the authors’ experience the primary reason for failure of surgical treatment of cruciate and collateral ligaments injuries is unrecognized posteromedial or posterolateral lesions, and this failure to diagnose and evaluate properly can result in a host of complications.…”
Section: Discussionmentioning
confidence: 95%